2000
DOI: 10.1515/jpem.2000.13.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hyperinsulinemic Hypoglycemia of Infancy: Long-Term Outcome Following Subtotal Pancreatectomy

Abstract: These results suggest that children with early-onset hypoglycemia have more severe hyperinsulinism than those with late-onset hypoglycemia. The former require 95% Px for maintaining euglycemia, but long-term complications with diabetes may be common. In contrast, the latter require lower percentage Px which may reduce the incidence of diabetes in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…However, technical difficulties in neonates often limit the usefulness of some of these techniques. It has also been suggested that those with later‐onset hyperinsulinsim requiring surgery may require lesser pancreatectomy 35 . Postoperatively, either hypoglycaemia or diabetes can develop transiently but, more importantly, there is a risk of permanent IDDM developing 30,36–38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, technical difficulties in neonates often limit the usefulness of some of these techniques. It has also been suggested that those with later‐onset hyperinsulinsim requiring surgery may require lesser pancreatectomy 35 . Postoperatively, either hypoglycaemia or diabetes can develop transiently but, more importantly, there is a risk of permanent IDDM developing 30,36–38 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, repeated episodes of severe, prolonged, sublethal hypoglycemia can result in permanent neurological damage, including developmental delay, mental retardation, and/or focal CNS deficits. Complications of neonatal hyperinsulinism are found in up to 50% of survivors, and this incidence has changed little during the past 20 years, reflecting the major problems that are faced in managing and treating this condition (5,8,9,29,166,173,181,196,201,253,284,313).…”
Section: Early Complications Of Hyperinsulinism In Infancymentioning
confidence: 99%
“…Extent of pancreatectomy has been the point of intensive discussion over the last 20 years [23,58,64,69,83,110,120]. Whereas in focal disease a limited resection of the focal area with preservation of as much pancreas as possible is performed, extension of surgery for diuse disease up to complete pancreatectomy results in an increasing risk of developing diabetes mellitus [15,62,69].…”
Section: Treatmentmentioning
confidence: 99%
“…Whereas in focal disease a limited resection of the focal area with preservation of as much pancreas as possible is performed, extension of surgery for diuse disease up to complete pancreatectomy results in an increasing risk of developing diabetes mellitus [15,62,69]. A recent study reported the occurrence of diabetes in 67% of patients after a >95% pancreatectomy [15].…”
Section: Treatmentmentioning
confidence: 99%